Origins, growth and future of geography to the memory of Prof. Drs. Kardono Darmoyuwono - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1984)
Numerous investigators and voyagers have, since the early days of exploration, contributed to our knowledge of the geography of the territory covered by the Republic of Indonesia. Their publications are a primary source from which ultimately modern geography has emerged. It is not possible to mention the names of all these explorers, firstly because the list would be too long, and secondly because it could be difficult to draw a sharp boundary between geography and non-geography. In fact, most of them were not specialists in the modern sense of the word, but generalists, which was in accordance with the concepts and the state-of-the-art then prevailing. An outstanding example from the 18th century is the well-known "Amboinsche Rariteitenkamer", published by Rumphius (1805). The three-volume classic "Java zijne gedaante, zijn plantentool en inwendige bouw" by Junghuhn (1853), and "Java" by Veth (1903)